Basomedial amygdala activity in mice reflects specific and general aversion uncontrollability. (9th January 2021) - Ineichen, Christian; Greter, Alexandra; Baer, Mischa; Sigrist, Hannes; Sautter, Eva; Sych, Yaroslav; Helmchen, Fritjof; Pryce, Christopher R.
Abstract: Learning adaptive behaviour to control aversion is a major brain function. Detecting the absence of control is also important, although chronic uncontrollable aversion can impact maladaptively on stimulus processing in general. The mouse basomedial amygdala (BMA) contributes to aversion processing with high BMA activity associated with active behavioural responding. The overall aim of the present study was to investigate the associations between aversion (un)controllability, BMA activity and behaviour. Fibre photometry of GCaMP6‐expressing BMA neuron populations was applied in freely behaving adult male mice during exposure to mild electrical shocks, and effects of specific or general (un)controllability were investigated. In a discrete learned helplessness (LH) effect paradigm, mice underwent discrete sessions of pre‐exposure to either escapable shock (ES) or inescapable shock (IES) followed by an escape test. IES mice acquired fewer escape attempts than ES mice, and this co‐occurred with higher aversion‐related BMA activity in the IES group. After 30 days, ES and IES mice were allocated equally to either chronic social stress (CSS)—exposure to continuous uncontrollable social aversion—or control handling (CON), and on days 5 and 15 underwent an IES session. CSS mice made fewer escape attempts than CON mice, and this was now associated with lower aversion‐related BMA activity in the CSS group. These findings suggest that mouse BMA activity is higher when discrete aversion is uncontrollable but becomes lower following chronic uncontrollable aversion exposure. Therefore, BMA activity could be a neural marker of adaptive and maladaptive states consequent to specific and general uncontrollability, respectively. Abstract : Ineichen et al. use fibre photometry to measure basomedial amygdala activity to e‐shock. Mice receiving inescapable e‐shock had an escape deficit and higher BMA activity compared to mice receiving escapable e‐shock. Mice undergoing chronic uncontrollable social stress made fewer escape attempts but now had lower BMA activity compared to controls. BMA activity appears to provide a neural marker of adaptive and maladaptive states consequent to specific and general uncontrollability, respectively.